Simultaneous control of Cydia molesta and Anarsia lineatella in peach orchards of Northern Greece by combining mating disruption and insecticide treatments - Kyparissoudas, D. S. (ENTOMOLOGIA HELLENICA, 1989)
Trials were carried out in 1987 and 1988 on the combined control of oriental fruit moth (OFM), Cydia molesta (Busck), and peach twig borer (PTB), Anarsia lineatella (Zell), in peach orchards in Northern Greece with Isomate-M pheromone dispensers (mating disruption technique) and insecticides against OFM and PTB, respectively. One application of the Isomate-M at a rate of 1,000 units per ha, and one application of the insect growth inhibitor (IGI) hexaflumuron 5 EC (200 ml f.p,/hl) or two sprays of fluvalinate 25 AF (60 ml f.p./hl) during June provided satisfactory control of OFM and PTB. Total damage per tree in the trials reached 1.0-3.6%, versus 1.4-3.0% in the conventionally sprayed orchards, while in unsprayed control blocks it was 14.4-23k. These encouraging results open possibilities for the combined control of these peach insects in Northern Greece.